Innovative reconstruction protocol for complex alveolar ridge defects in posterior mandible: Case Report and technical analysis - Feng, Jian; Jia, Kewen; Chen, Siyu; Ren, Sicong; Han, Yuzhu; Li, Mucong; Zhang, Yidi; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundKnife-edge ridges in posterior mandible present challenges for implant placement due to insufficient horizontal bone width and inadequate keratinized tissue, traditionally requiring secondary donor site surgery with associated morbidity.Case DescriptionA 46-year-old female with severe mandibular atrophy underwent two-stage reconstruction. First-stage surgery involved harvesting bone blocks from the knife-edge ridge, rotating them 180° counterclockwise, and securing for horizontal augmentation. After 7 months, second-stage surgery included implant placement with platelet-rich fibrin soft tissue augmentation using open-suture technique. Outcomes demonstrated horizontal bone gains of 4.3–4.8 mm, keratinized tissue increase of 2.9 mm, and absolute bone volume gain of 859.86 mm3. All three implants achieved successful osseointegration.Practical ImplicationsThis novel staged protocol integrates in situ bone grafting with PRF-based soft tissue augmentation, specifically designed for posterior mandibular knife-edge ridges. By systematically combining these techniques, it eliminates donor site morbidity while achieving clinically significant tissue augmentation, offering practitioners a comprehensive autologous reconstruction approach that addresses the unique anatomical constraints and dual tissue deficiencies characteristic of this challenging region.